2004
DOI: 10.1261/rna.7181105
|View full text |Cite
|
Sign up to set email alerts
|

Domain structure and three-dimensional model of a group II intron-encoded reverse transcriptase

Abstract: Group II intron-encoded proteins (IEPs) have both reverse transcriptase (RT) activity, which functions in intron mobility, and maturase activity, which promotes RNA splicing by stabilizing the catalytically active RNA structure. The LtrA protein encoded by the Lactococcus lactis Ll.LtrB group II intron contains an N-terminal RT domain, with conserved sequence motifs RT1 to 7 found in the fingers and palm of retroviral RTs; domain X, associated with maturase activity; and C-terminal DNA-binding and DNA endonucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
122
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 87 publications
(126 citation statements)
references
References 56 publications
3
122
1
Order By: Relevance
“…The RTs of group II introns and non-LTR retrotransposons contain seven conserved sequence blocks (RT-1-RT-7) characteristic of all RTs, but differ from retroviral RTs in having an N-terminal extension with conserved sequence block RT-0, as well as additional insertions in the RT and thumb domains, some with conserved structural features in group II intron and non-LTR-retrotransposon RTs (Xiong and Eickbush 1990;Malik et al 1999;Blocker et al 2005). Like group II intron RTs, non-LTR-retrotransposon RTs promote retrotransposition by using a target DNA-primed reverse transcription mechanism in which a cleaved DNA strand is used as a primer for reverse transcription of the element's RNA, and the cDNA initiation site is determined primarily by specific binding of the RNA template rather than by base pairing of a primer, as for retroviral RTs (Luan et al 1993;Zimmerly et al 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RTs of group II introns and non-LTR retrotransposons contain seven conserved sequence blocks (RT-1-RT-7) characteristic of all RTs, but differ from retroviral RTs in having an N-terminal extension with conserved sequence block RT-0, as well as additional insertions in the RT and thumb domains, some with conserved structural features in group II intron and non-LTR-retrotransposon RTs (Xiong and Eickbush 1990;Malik et al 1999;Blocker et al 2005). Like group II intron RTs, non-LTR-retrotransposon RTs promote retrotransposition by using a target DNA-primed reverse transcription mechanism in which a cleaved DNA strand is used as a primer for reverse transcription of the element's RNA, and the cDNA initiation site is determined primarily by specific binding of the RNA template rather than by base pairing of a primer, as for retroviral RTs (Luan et al 1993;Zimmerly et al 1995).…”
Section: Introductionmentioning
confidence: 99%
“…Like group II intron RTs, non-LTR-retrotransposon RTs promote retrotransposition by using a target DNA-primed reverse transcription mechanism in which a cleaved DNA strand is used as a primer for reverse transcription of the element's RNA, and the cDNA initiation site is determined primarily by specific binding of the RNA template rather than by base pairing of a primer, as for retroviral RTs (Luan et al 1993;Zimmerly et al 1995). It has been speculated that the N-terminal extension and/or other RT-and thumb-domain insertions in group II intron and non-LTR-retroelement RTs contribute to their distinctive properties, including higher processivity than that of retroviral RTs (Bibillo and Eickbush 2002a) and specific binding of the template RNA for initiation of reverse transcription (Chen and Lambowitz 1997;Bibillo and Eickbush 2002b;Blocker et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Our experiments with nicked DNA substrates confirm that bending results from RNP interactions with the 3' exon and not from bottom-strand cleavage itself ( Figure 8). As indicated previously, three-dimensional modeling predicted that the IEP could not interact simultaneously with its target sequences in the 5'-and 3'-exons unless the DNA is bent strongly in the complex (17).…”
Section: Discussionmentioning
confidence: 60%
“…Docking of target DNA onto this three-dimensional model showed that the DNA target sequence is too long for the LtrA protein to bind simultaneously to its interaction sites in the distal 5'-exon and 3'-exon regions unless the DNA is strongly bent in the complex (17). These findings raised the possibility that bendability of the DNA target site might significantly influence the efficiency of the integration reaction.…”
mentioning
confidence: 99%
“…4 However, previous studies with RNPs assembled in vitro and in vivo also suggest that LtrA binds RNA as a dimer. 7,[19][20][21] Given this conundrum, further analysis is in order. One possibility is that the RIM structure represents a truncated protein from which a sequence that inhibits dimerization has been deleted and that full-length RIM also binds the intron RNA as a monomer.…”
Section: The Monomer-dimer Conundrummentioning
confidence: 99%